Quatre traductions inédites de Michaux - Luca Bevilacqua; Giuseppe Girimonti Greco; Giuseppe Zuccarino (Revue Italienne d'Etudes Françaises)
Three translators, Luca Bevilacqua, Giuseppe Girimonti Greco and Giuseppe Zuccarino, meet to work on four previously unpublished translations of Michaux. In the diversity of their approaches, they adopt several solutions that highlight the heterogeneous and hybrid nature of the texts, in verse and prose, by the Franco-Belgian poet. The four translations presented here are preceded by an introduction in which Luca Bevilacqua reviews Michaux’s diffusion in Italy and introduces his translations of “Je suis né troué” and “Nous autres”. The translations of “Une vie de chien” and “The Thin Man’’ are commented by their respective translators. In the appendix, the transcription of Franco Calamandrei’s translation of “Une vie de chien”.